2011
DOI: 10.1021/ol2015972
|View full text |Cite
|
Sign up to set email alerts
|

Monoalkylation of Acetonitrile by Primary Alcohols Catalyzed by Iridium Complexes

Abstract: The monoalkylation of acetonitrile by primary alcohols was achieved in a one-pot sequence in the presence of iridium catalysts. A diversity of nitriles has been obtained from aryl- and alkyl-methanols in excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…[3] In last decade, following the hydrogen borrowing methodology transition metal catalysed severalC ÀCa nd CÀNb ond forming reactions were explored. [4] Inspired by this protocol, synthesis of alkylated nitrile by replacing the alkyl halidesw ith alcohols as greener alkylat-ing agentsw as explored by various groups using different precious Ir, [5] Ru, [6] Rh, [7] Pd [8] and Os [9] metal based complexes (Scheme 1). Recently Mn catalysed a-olefination and a-alkylation of nitriles using primary alcohols were described by Milstein et al and Maji et al respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3] In last decade, following the hydrogen borrowing methodology transition metal catalysed severalC ÀCa nd CÀNb ond forming reactions were explored. [4] Inspired by this protocol, synthesis of alkylated nitrile by replacing the alkyl halidesw ith alcohols as greener alkylat-ing agentsw as explored by various groups using different precious Ir, [5] Ru, [6] Rh, [7] Pd [8] and Os [9] metal based complexes (Scheme 1). Recently Mn catalysed a-olefination and a-alkylation of nitriles using primary alcohols were described by Milstein et al and Maji et al respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the difficulty of the intramolecular alkylation of nitriles with halides, we envisaged alkylation by using alcohols, as the alkylation of activated nitriles with alcohols [8] has been demonstrated, and more recently, the alkylation of non-activated nitriles [9] was shown. These alkylations were realized by using Ir and Ru complexes that serve as efficient catalysts for hydrogen transfer, [10] producing aldehydes or ketones that undergo an aldolization/crotonization/reduction to produce the alkylated nitriles.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1981, when Grigg and co‐workers first used RuH 2 (PPh 3 ) 4 as a catalyst in the alkylation of nitriles with alcohol, a lot of effort has been devoted to exploring various catalysts, including Ru, Rh, Ir, Pd, Os, Fe, and Mn. Of these, Ru complexes are the most reported, for example Gunanathan's group reported that Ru(PNP) (PNP = bis(2‐(diphenylphosphino)‐ethyl)amine) pincer complex showed good activity for α ‐alkylated reaction of arylmethyl nitriles .…”
Section: Introductionmentioning
confidence: 99%